An Analysis of Maxims Violation Acted by the Main Characters in the "Tilik" Short Film - Albiansyah Albiansyah; Didin Nuruddin Hidayat; Alek Alek (OKARA: Jurnal Bahasa dan Sastra, 2021)
The maxims violation often occurred intentionally or unintentionally in daily human conversation. This study analyzes the maxim violation in one of the Indonesian short films, 'Tilik,' in which Bu Tejo and Yu Ning were the main characters. This present study aims to describe the phenomena of maxim violation by the main characters. It is qualitative descriptive research. The technique used in collecting speech was the note-taking technique, and data were taken from the transcript of the main characters' utterances. Then, to analyze the maxim violation revealed in the short film, the researchers used the Cooperative Principles from Grice's theory, which has four kinds: quality, quantity, relevance, and manner. The findings indicated that the main characters carried out all four maxim types violations. The highest maxim violation found were the quantity and quality maxim. Some certain implicatures were contained when the main character of this short film reckoned to convey the implicit message, ensure the hearer, award astonishment, take for concern, and evade the problem. The study also exposed the rationales behind violating maxims, which helped create more straightforward communication and developing further explanations. Further studies can include more extensive data to obtain more robust findings.